2018 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2018
DOI: 10.1109/icassp.2018.8462103
|View full text |Cite
|
Sign up to set email alerts
|

Robust Full-Sphere Binaural Sound Source Localization

Abstract: We propose a novel method for full-sphere binaural sound source localization that is designed to be robust to real world recording conditions. A mask is proposed that is designed to remove diffuse noise and early room reflections. The method makes use of the interaural phase difference (IPD) for lateral angle localization and spectral cues for polar angle localization. The method is tested using different HRTF datasets to generate the test data and training data. The method is also tested with the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…In reverberant environments, the total impulse response is comprised of the HRIR and an additional component provided by the acoustic reflections, ζ (t). The acoustic reflections consist of early reflections, which have directionality and later reflections which are diffuse [2,7]. If this sound is recorded at the ears, the recording equipment and procedure may also introduce convolutive noise, ν ζ (t) and additive noise, χ ζ (t).…”
Section: Proposed Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In reverberant environments, the total impulse response is comprised of the HRIR and an additional component provided by the acoustic reflections, ζ (t). The acoustic reflections consist of early reflections, which have directionality and later reflections which are diffuse [2,7]. If this sound is recorded at the ears, the recording equipment and procedure may also introduce convolutive noise, ν ζ (t) and additive noise, χ ζ (t).…”
Section: Proposed Methodsmentioning
confidence: 99%
“…To account for phase circularity, the PDF is estimated using all aliases of the IPD in the range (−3π, 3π] for each time-frequency unit. In [2], univariate kernel density estimation was used to estimate the PDF of the IPD in each frequency band. For the proposed method, it was found that the IPD of the direct component of the sound was better estimated by using bivariate kernel density estimation to estimate the PDF of the IPD as a function of frequency:…”
Section: Proposed Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pang et al [1] put forward with reverberation weighting and a more generalized parametric model to further improve the localization performance in the reverberant and noisy environments. A full-sphere binaural localization method is proposed in [11], which applies the Interaural Phase Difference (IPD) for lateral localization and spectral cues for polar angle localization. Although the HRTFs for the training and test sets are captured in different rooms, the models of the dummy head are the same.…”
Section: Introductionmentioning
confidence: 99%